Characterization and formulation of bio-active fraction of Moringa oleifera Lam. leaves extract and its protective potential against acetaminophen toxicity - Karthivashan, Govindarajan (2016)
Moringa oleifera (MO) is a well-known and widely distributed tropical species of Moringaceae family. Its leaves possess an excellent nutritional profile and an impressive range of therapeutic properties. Recently, the investigations on pharmaceutical properties of MO leaves get expanded due to its enriched antioxidant potential. Though numerous study reports focused on its therapeutic efficacy, the responsible active compounds and its underlying molecular mechanism of action has not been determined yet which hold a setback for researchers to explore its exact therapeutic potential. Acetaminophen (APAP) overdose is a worldwide leading cause of acute liver failure and drug-induced hepatotoxicity. During APAP overdose, majority of the drug is converted by the cytochrome P450 (CYP 450 - 2E1/1A2) enzymes to the reactive toxic metabolite, N-acetyl-pbenzoquinoneimine (NAPQI) that depletes GSH level and covalently binds to the other cellular proteins and induce hepatocyte death/acute liver failure. Currently, the most effective therapy for APAP overdose is Nacetylcysteine (NAC), which replenishes glutathione level and enhances hepatic recovery. However, NAC has few significant limitations such as time constraints and reversal of GSH level alone may not be sufficient to arrest progress of APAP hepatotoxicity. This drives scientists/researchers in exploring for an alternative safe and effective therapy. In this study, the optimal MO gradient leaf extract has been obtained as 90% hydro-ethanolic solution based upon in vitro antioxidant assays and the active compounds responsible for its elite activity has been determined as quercetin, kaempferol, apigenin and multiflorin-B through chromatographic analysis. The underlying mechanism of action of 90% hydro-ethanolic MO leaf extract has been evaluated in Balb/c mice inflicted with lethal dose of APAP for hepato- and nephro-toxicity. The MO leaf extract effectively protects the liver through suppression of CYP 450 isoenzymes and in both liver and kidney through regulation of antioxidant enzymes level and modulation of inflammatory cytokines thereby hindering the further exacerbation of necrotic and renal tubular damage respectively. Further, 90% MO leaf crude extract was fractionated through liquid-liquid partition technique. Among the obtained solvent fractions, ethyl acetate (EA) fraction revealed the highest antioxidant activity evidently due to the presence of quercetin, kaempferol and apigenin which has been identified and quantified with commercial standards using HPLC analysis. Wherein, kaempferol was expressed in higher concentration with 263.86 μg, followed by apigenin and quercetin with 82.64 and 66.89 μg respectively, per mg of MO leaves EA fraction. Soy phosphatidylcholine (PC) is a bifunctional complex comprises of lipophilic phosphatidyl moiety and hydrophilic choline moiety. Naturally, flavonoids and phenolic compounds got affinity to bind with PC molecule resulting in a cell like lipid compatible molecular complex. In accordance, the EA fraction and its three major flavonoids quercetin, kaempferol and apigenin has been successfully loaded in PC molecule to retain its synergism and enhance bioavailability. Further its physico-chemical parameters, invitro drug release and hepato-protective potential against APAP inflicted hepatotoxicity in HepaRG cell line has been evaluated. The findings of this study has evidently suggested that MO leaves extract and its EA fraction loaded phospholipid complex can be implied as an effective antidote against APAP intoxication as it hinders/suppresses/modulates various key biomarkers involved in APAP hepatotoxicity pathway.